PEMBERITAAN RAMAH GENDER PADA ARTIKEL KEKERASAN SEKSUAL TERHADAP PEREMPUAN DI MEDIA FEMINIS MAGDALENE - Ranti Dinda Cintya; Nurul Hasfi; Primada Qurrota Ayun (Interaksi Online, 2023)
News related to sexual violence against women in mainstream media often lacks a gender perspective and fails to adhere to the applicable journalistic code of ethics. As a result, this contributes to the perpetuation of the stigma of victims in society and hinders efforts to eradicate cases of sexual violence. Magdalene is one of the feminist media that has the mission of fighting patriarchy and bringing feminist issues closer to the public. This research aims to look at the framing of news related to sexual violence issues in the Magdalene media and how the news can accommodate the principles of gender journalism. The theories used are Agenda Setting Theory and Social Reality Construction Theory and Robert N. Entmant's framing analysis model is used as the research method. The research results show framing Magdalene has the propensity to voice difficulties associated with the subject of sexual violence by looking at it from the victim's perspective and the injustices encountered by the victim. Based on the results of framing analysis on 21 articles on sexual violence against women in Magdalene, four representations were found to consist of, the issue of sexual violence as a result of strong patriarchal ideology, the issue of sexual violence has not been handled because it is still considered a private issue, the legal system for cases of sexual violence in Indonesia has not been in the perspective of the victim, and the handling of sexual violence cases in Indonesia has not taken the side of the victim. The whole article at Magdalene related to the issue of sexual violence against women have accommodated the principles of journalism from a gender perspective, this is demonstrated by the existence of a perspective that is pro-victim, efforts to prioritize the psychological condition of victims and their recovery, as well as advocacy aimed at making social changes to help victims get better treatment in their environment and society, and the fulfillment of human rights that provide legal protection and justice. In addition, it is displayed through selecting topics that focus on gender inequality, including labeling in society, stereotypes against female victims, and marginalization and subordination.